Patients with CHF find decision aid for ACP helpful and computer-generated advance directive accurate. Issue 2 (1st June 2012) - Green, MJ; Hensel, J; Farace, E; Whitehead; Lehmann; Levi, BH
Abstract : The fluctuating clinical course of congestive heart failure involves recurrent medical crises and readmission rates of ∼50% within 6 months following hospital discharge. The consequent focus on acute care measures often results in insufficient emphasis on advance care planning (ACP). This pilot study examined whether an interactive computer-based decision aid can effectively address this need by helping individuals with advanced CHF engage in ACP. Adults with advanced congestive heart failure (i.e., Stage 3 or 4) were recruited from a single cardiovascular clinic; screened for cognitive ability, moderate/severe depression, and ≥8 th grade reading level; and asked to complete a computer program, pre-/post-questionnaires, and a follow-up telephone interview. The 24 study participants (mean age = 65 years, 83% male) reported minimal decisional conflict in making ACP decisions (mean=30, 16=least conflict, 80=greatest conflict) and high satisfaction with the computer program (mean=9.3, 1=least satisfied, 10=most satisfied), decisions they made (mean=27, 6=least satisfied, 30=most satisfied), and the accuracy of the computer-generated advance directive (6.6, 1=not at all accurate, 7=extremely accurate). Additionally, participants' knowledge regarding ACP increased significantly (43% → 62%, p<0.001) with no decrease in hopefulness (p=0.49), and the majority (87%) went on to discuss their ACP wishes with family and friends. These preliminary findings show that a computer decision aid program is well-accepted by patients with advanced congestive heart failure, and can help such individuals engage in ACP, increase their knowledge about ACP, create accurate advance directive documents, and discuss their wishes with family and friends.